A common humoral background of intraocular and arterial blood pressure dysregulation. (4th March 2018) - Skrzypecki, Janusz; Grabska-Liberek, Iwona; Przybek, Joanna; Ufnal, Marcin
Abstract: Background: It has been postulated that intraocular pressure, an important glaucoma risk factor, correlates positively with arterial blood pressure (blood pressure). However, results of experimental and clinical studies are often contradictory. It is hypothesized that, in some hypertensive patients, disturbances in intraocular pressure regulation may depend on biological effects of blood borne hormones underlying a particular type of hypertension, rather than on blood pressure level itself. Review: This review compares the effects of hormones on blood pressure and intraocular pressure, in order to identify a hormonal profile of hypertensive patients with an increased risk of intraocular pressure surge. The PUBMED database was searched to identify pre-clinical and clinical studies investigating the role of angiotensin II, vasopressin, adrenaline, noradrenaline, prostaglandins, and gaseous transmitters in the regulation of blood pressure and intraocular pressure. Results: Studies included in the review suggest that intraocular and blood pressures often follow a different pattern of response to the same hormone. For example, vasopressin increases blood pressure, but decreases intraocular pressure. In contrast, high level of nitric oxide decreases blood pressure, but increases intraocular pressure. Conclusions: Arterial hypertension is associated with altered levels of blood borne hormones. Contradicting results of studies on the relationship between arterial hypertension and intraocular pressure might be partially explained by diverse effects of hormones on arterial and intraocular pressures. Further studies are needed to evaluate if hormonal profiling may help to identify glaucoma-prone patients.